In Search of Environmental Ethics for the Theory of Ecological Education - Gola, Beata (Studia Ecologiae et Bioethicae, 2016)
Undoubtedly, the contemporary problems of ecological philosophy and eco- pedagogy deal with questions about the real presence of the philosophical bases for the ecological upbringing of children and youth. Therefore, can different conceptions of environmental ethics (e.g., anthropocentric ethics, bio-centric ethics, holistic ethics) be found in the contemporary theory of ecological upbringing? A partial answer to the question can be provided by educational programs implemented in the process of formal education (e.g. content analysis of school textbooks in specific subjects), as well as educational activities undertaken by the selected centers in the system of non-formal education (content analysis of teaching materials). The directory of ecological values distinguished from the tested materials can also be used in the search for answers to this question. This directory describes the man/ natural environment relationship, while these ecological values are strongly articulated in certain eco-ethics positions.